(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Scientific knowledge about people’s well-being and health after the medical or surgical path of gender resignation is still neglected. Studies have shown how hormone therapies, minority stress, and unhealthy lifestyles can give transgender people an increased risk of developing multiple diseases compared to the general population. It is essential to reflect on the critical issues of the healthcare system, in order to personalize public health actions towards this user group, which requires an integrated and continuous approach, sensitive to individual differences and free from prejudice and discrimination, with a view to equity of care.